Arctic National Wildlife Refuge development : joint hearing before the Subcommittee on Fisheries and Wildlife Conservation and the Environment of the Committee on Merchant Marine and Fisheries and the Subcommittee on Water and Power Resources of the Committee on Interior and Insular Affairs, House of Representatives, One Hundredth Congress, first session . November 17, 1987. - United States. Congress. House. Committee on Merchant Marine and Fisheries. Subcommittee on Fisheries and Wildlife Conservation and the Environment.; United States. Congress. House. Committee on Interior and Insular Affairs. Subcommittee on Water and Power Resources. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., Congressional Sales Office, U.S. G.P.O., 1988)
Mode of access: Internet.